Penerapan Metode Fuzzy Mamdani dan Fuzzy Tsukamoto Dalam Menentukan Harga Mobil Bekas - Siti Maryam; Efori Bu'ulolo; Edizal Hatmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The Mamdani method and the Tsukamoto method are the methods most frequently encountered when discussing fuzzy methodologies. In Tsukamoto's method, each consequent to the rule in the form of IFTHEN must be represented by a fuzzy set with a monotonous membership function as the result. Many problems can be solved by using these two methods, one of which helps in determining the price of a used car. The presence of cheap cars that are increasingly incessant also affects the business of selling used cars because people have perceptions and tend to trust the types and brands of cars that have been tested for durability. This condition is also a problem at CV. Citra Kencana Mobil to determine the price of used cars. The calculation results show that the fuzzy mamdani method estimates the price of used cars to be cheaper than the Tsukamoto method.